The World of Rhabdoviruses - Fu, Z.F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
(Draft) In this volume the unique and common features of rhabdoviruses, particularly their morphological, molecular, and pathogenic characteristics, and their phylogenetic relationships are reviewed. Rhabdoviruses have a very wide host range and have been isolated from plants, insects, and almost from all vertebrates including fish and primates. The Rhabdoviridae family consists of six genera which have all been associated with diseases. While rhabdoviruses that are etiological agents of human diseases can cause serious public health problems, other members of this family that infect domestic livestock and agricultural plants can also cause enormous economic loss. .
Genetic Comparison of the Rhabdoviruses from Animals and Plants -- Australian Bat Lyssavirus: A Recently Discovered New Rhabdovirus -- Pathogenesis of Rabies -- Bovine Ephemeral Fever in Australia and the World -- Fish Rhabdoviruses: Molecular Epidemiology and Evolution -- Reverse Genetics on Fish Rhabdoviruses: Tools to Study the Pathogenesis of Fish Rhabdoviruses -- Plant Rhabdoviruses -- Recombinant Rhabdoviruses: Vectors for Vaccine Development and Gene Therapy.
Keywords: Virology; Virology